High gain miniaturised photonic band gap terahertz antenna for size-limited applications. Issue 2 (3rd April 2019) - Tripathi, Subodh Kumar; Kumar, Ajay
ABSTRACT: Graphene has special properties that can be utilised in the design of terahertz (THz) range antennas for wireless network applications. A graphene-based photonic band gap (PBG) THz Patch Antenna is proposed. A reduced size antenna showing better performance is reported by utilisation of graphene with a PBG structure. PBG structures in the presence of a graphene patch with and without a slotted ground are also analysed. The proposed antenna is miniaturised still maintaining good gain (7.99 dB) and good directivity (8.42 dB) in comparison to work reported in the literature. Volume of the proposed antenna is reduced to 0.05 mm 3 which is suitable for size-limited future applications such as Wireless Networks on Chip and Wireless Nano-Sensor Networks.